DETERMINANTS OF ENTREPRENEURSHIP DEVELOPMENT ON THE EXAMPLE OF GOSTYCYN COMMUNE - Zawisza, Sławomir; Dończyk, Małgorzata (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article presents the results of surveys, carried out in September 2009, among randomly selected, 113 entrepreneurs. Documents provided by the commune office and the Internet sources concerning this subject, were analyzed as well. The purpose of this work was to examine the conditions for development of entrepreneurship on the territory of a typical rural commune such as Gostycyn in the Kujawsko-pomorskie Province. The respondents were of the opinion that the influence of their activities on creation of new jobs, boosting local economy and the demand for products and services as well as infrastructure development, was rather insignificant. Competition on the local market was rated as average. More than half of the respondents confirmed cooperation with other companies. They also indicated difficulties in running a business, including: bureaucracy, taxes and bills, competition, maintenance of financial availability and poor customer’s demand. Barriers disrupting development of entrepreneurship which were most frequently mentioned included: difficulties in obtaining low interest credits, high taxes, high delivery costs and dispersion of customers. Location near the commune main road was indicated by most interviewers as providing a good chance for development of entrepreneurship. A considerable group of the surveyed entrepreneurs noticed improvement in conditions for running a business in the area of Gostycyn commune after Poland’s accession to the structures of the European Union, in 2004. Since then, the number of respondents taking advantage of the support provided by the Union, has increased significantly.